Trabalho voluntário e biografia : compreendendo a constituição da ação de engajamento no voluntariado através do método da narrativa biográfica - Samuel, Fabian Sichonany (2016)
This work aims to contribute to studies on the subject of volunteering, given the importance that the movement is gaining in Brazil, especially after the period following the re-democratization of the country. At first, it was analyzed the development of the activity in Brazil and its social implications, particularly as regards the qualifications of social ties in the face of growing individualism. So, given the importance of this activity, in a second step, still in a theoretical way, the analysis focused on the social actions and how they are produced. For this purpose, it was used the theory of Alfred Schutz action. It is understood, in this study, the engagement action in volunteering as a social action according to Schutz. This study sought to understand how the reasons and motives for engaging in volunteering are built through the life experiences of social actor, seeking to reveal the because motives (or biographic motives). This study conducted five interviews with people who volunteer in institutions of civil society, of which the analysis and presentation that were oriented by the method of Narrative Biographical developed by Fritz Schütze and perfected by Gabriele Rosenthal, focused on one of them. Empirical research with Fernanda has revealed that the engagement action in volunteering is constructed biographically through the relationship between the biographically determined situation and the world of common sense. Biographical experiences both change the interpretations of social actor on the world and guide him in the decision making process to engage in voluntary activity. In addition, we glimpse a singular biographical path, composed of four main biographical moments, interconnected, which, added to a context where the culture of volunteering is widespread, favored Fernanda on the occasion of his decision to become a volunteer. The biographee managed to turn the disease and suffering in personal growth factor, through the contact and socialization in a spiritist universe of meaning, and that was determinant for her in order to prepare her action project.